PROSES KOORDINASI KETERTIBAN UMUM DI KELURAHAN SIANTAN HILIR KECAMATAN PONTIANAK UTARA - Chahyadi E.01108020, Dwi (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The title of this article is the Public Order Process Coordination in Lower Village District Siantan North Pontianak. This article dilator background by the number of buildings on land that is not in accordance with the functions and use established by the conduct trades for their subsistence and aim to gain employment with limited land, this is usually as practiced by the merchants sidewalk or commonly refer to as street vendors. Formulation of the problem in this article, namely:'' How the Process Implementation Coordinating Public Order law in village district Siantan Lower North Pontianak ". Purpose of this article is intended to study and analyze coordination of agencies involved in the implementation process in the Public Order laws regulate street vendors in the Village of North Pontianak District Siantan downstream. The method used in this paper is a descriptive type.The results obtained from this study is that the implementation is not optimal coordination between the village, district and police units in the implementation process pamongparja Regulation on public order No 3 of 2004 and the lack of clarity of compensation that is given from the relevant agencies. To the need for the Civil Service Police Unit, District, Sub-District, increasing the intensity of the meeting or meetings in order to coordinate efforts to implement the law optimizers Public Order No. 3 of 2004 in the Village District Siantan Lower North Pontianak.Keywords: Public Order, Street Vendors, and Executive Coordination.